1996
DOI: 10.1097/00005373-199608000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Dilational Tracheostomy

Abstract: Surgeons can rapidly perform PDT at the bedside with a lower risk of complications than open tracheostomy and at a significantly reduced patient charge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 31 publications
11
108
5
Order By: Relevance
“…Moreover, it adds complexity to the procedure and risks potential endoscope damage. Like other authors, we found endoscopic guidance useful during the learning phase [33,37] and in dif®cult patients. However, we do not recommend its routine use with the Griggs technique because the larger soft tissue stoma created by the forceps allows easier identi®cation of the tracheal level and the midline without additional blunt dissection [29,38].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, it adds complexity to the procedure and risks potential endoscope damage. Like other authors, we found endoscopic guidance useful during the learning phase [33,37] and in dif®cult patients. However, we do not recommend its routine use with the Griggs technique because the larger soft tissue stoma created by the forceps allows easier identi®cation of the tracheal level and the midline without additional blunt dissection [29,38].…”
Section: Discussionsupporting
confidence: 83%
“…Using endoscopic examination 3 months after removal of the tracheostomy tube, we found severe tracheal narrowing at the stoma site in 5% of the survivors and granulation tissue at the stoma site without the need for treatment in 9%. This compares favourably with stenosis rates of 0±5% in other series [40]. Rates of other complications are similar for percutaneous and open tracheostomy [41].…”
Section: Discussionsupporting
confidence: 70%
“…The current preoperative intubation and postoperative observation times match results in international studies (Table I). [12][13][14]19,22,25 Also, the great variation in cannulation time is reflected in literature. 15,[20][21][22]25 In contrast to other studies, patients were not selected, and 88 (26.7%) high-risk patients, of whom 13 (4%) had acute dyspnea, were included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Of all tracheotomies, 72.9% were performed in the first 3 weeks after endotracheal intubation (Table II). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The period of cannulation varied strongly (range, 1-730 days) (n ¼ 291). In 146 patients (49.5%), the cannula remained in situ for a time period between 1 week and 1 month (20.3% 1-7 days and 25.3% 30-90 days).…”
Section: Clinical Time Intervalsmentioning
confidence: 99%
“…It was introduced as a preferred, safe and less-invasive bedside method that is alternative for open surgical tracheostomy. The rate of overall perioperative complications is 19% 3 . Although adverse events are relatively uncommon, serious life threatening complications can arise from this bedside procedure.…”
Section: Introductionmentioning
confidence: 99%